Prevalence of chronic rhinosinusitis and its relating factors in patients with bronchiectasis: findings from KMBARC registry - Yu, Iseul; Yong, Suk Joong; Lee, Won-Yeon; Kim, Sang-Ha; Lee, Hyun; Kim, Deog Kyeom; Oh, Yeon-Mok; Lee, Ji-Ho (The Korean journal of internal medicine, 2022)
Background/Aims: Patients with bronchiectasis often present with respiratory symptoms caused by chronic rhinosinusitis (CRS). However, studies on the prevalence of CRS and its relationship with bronchiectasis are limited.Methods: The baseline characteristics of patients with bronchiectasis recruited from the Korean Multicenter Bronchiectasis Audit and Research Collaboration were analyzed. CRS diagnosis was determined by a physician, on the basis of medical records, upper airway symptoms, and/or radiologic abnormalities. Questionnaires for quality of life, fatigue, and depression were administered when patients were stable for a minimum of 4 weeks after the bronchiectasis exacerbation.Results: The prevalence of CRS was 7.1% (66/931). Patients with CRS were significantly younger than those without CRS (60.5 ± 10.7 years vs. 64.6 ± 9.3 years, p = 0.001). Idiopathic bronchiectasis was more common in patients with CRS compared to those without CRS (53.0% vs. 36.0%, p = 0.006). Lung function, inflammatory markers, exacerbations, bronchiectasis severity, and scores for quality of life, fatigue, and depression did not differ between the two groups. In a logistic regression analysis, CRS was associated with age of bronchiectasis diagnosis (odds ratio [OR], 0.96; 95% confidence interval [CI], 0.94 to 0.99; p = 0.003) and idiopathic bronchiectasis (OR, 1.95; 95% CI, 1.12 to 3.34; p = 0.018).Conclusions: The prevalence of CRS was relatively low. CRS was not associated with the severity or clinical outcomes of bronchiectasis. Early diagnosis and idiopathic etiology were associated with CRS. Our findings reflect the low recognition of CRS in the clinical practice of bronchiectasis and highlight the need for awareness of CRS by adopting objective diagnostic criteria.